Innovative Technology-Based Learning Methods to Increase Student Engagement in Primary Schools - Hasbullah, Bahmid (PT Inovasi Pratama Internasional, 2025)
This research aims to explore the innovation of technology-based learning methods in improving student engagement in primary schools. Qualitative research methods were used with a case study approach in three primary schools in a major Indonesian city. Data were collected through in-depth interviews with teachers, classroom observations, and analysis of learning documents. The results show that the use of technology such as interactive learning applications, digital platforms, and multimedia tools can improve learning motivation, active participation, and student interaction during learning. However, challenges such as infrastructure availability, teacher training, and technical constraints were also found. This research provides recommendations for effective implementation of technology in learning, including continuous teacher training and student needs-based content development.